1991
DOI: 10.1007/bf01047112
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical localization of adenylate cyclase activity in rat olfactory cells

Abstract: Adenylate cyclase activity was demonstrated in the cilia, dendritic knob and axon of rat olfactory cells by using a strontium-based cytochemical method. The activity in the cilia and the dendritic knob was enhanced by non-hydrolyzable GTP (guanosine triphosphate) analogues and forskolin, and inhibited by Ca2+, all in agreement with biochemical reports of the odorant-sensitive adenylate cyclase. The results support the hypothesis of cyclic AMP working as a second messenger in olfactory transduction and imply th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…An odorant-receptor complex formed in the ciliary membrane is presumed to activate adenylate cyclase in this region in a G-protein-dependent manner and produce cyclic AMP, which, in turn, opens a cyclic nucleotide-gated channel permitting inward current flux. Our recent cytochemical study, which demonstrated adenylate cyclase activity in the cilia, and to some degree in the dendritic knob of rat olfactory cells, supported the above hypothesis (Asanuma & Nomura, 1991). Since the termination of olfactory signals must 0018-2214 9 1993 Chapman & Hall require decomposition of cyclic AMP, we thought it worthwhile to examine the localization of cyclic AMP degrading enzymatic activity in olfactory cells.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…An odorant-receptor complex formed in the ciliary membrane is presumed to activate adenylate cyclase in this region in a G-protein-dependent manner and produce cyclic AMP, which, in turn, opens a cyclic nucleotide-gated channel permitting inward current flux. Our recent cytochemical study, which demonstrated adenylate cyclase activity in the cilia, and to some degree in the dendritic knob of rat olfactory cells, supported the above hypothesis (Asanuma & Nomura, 1991). Since the termination of olfactory signals must 0018-2214 9 1993 Chapman & Hall require decomposition of cyclic AMP, we thought it worthwhile to examine the localization of cyclic AMP degrading enzymatic activity in olfactory cells.…”
Section: Introductionmentioning
confidence: 72%
“…This seems to suggest, together with the observation of adenylate cyclase activity in the cilia and somewhat in the dendritic knob (Asanuma & Nomura, 1991), that cyclic AMP, which is produced in the dendritic terminal (mainly in/the cilia), acts predominantly in its original site but ~fhat some of it may also reach and act upon the dendritic and somatic membrane. This idea is consistent with the electrophysiological studies which indicate that the cyclic nucleotide-gated channels of olfactory cells exist densely in the ciliary membrane and at a low density in the dendrosomatic membrane (Firestein et al, 1991b;Kurahashi & Kaneko, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, fixation inhibits the activity and responsiveness of adenylate cyclase to a variable degree depending on the nature of the fixative and on the type of tissue (Poeggel et aI., 1984). Moreover, quantitative biochemical analyses have demonstrated that fixation in either glutaraldehyde alone (Schultze, 1982;Ogawa eta]., I987) or in a mixture of paraformaldehyde and glutaraldehyde (Asanuma & Nomura, 1991) substantially reduces adenylate cyclase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In rat olfactory mucosa, AC activity was detected ultracytochemically by stimulation with nonhydrolysable GTP analogues and forskolin (Asanuma & Nomura, 1991) and an AC that mediates olfactory transduction for a wide variety of odorants was identified in olfactory receptor cells of bullfrog and rat (Anholt, 1988;Lowe et al, 1989;Pfeuffer et at., 1989;Ronnett et al, 1991). If the localization of AC reaction product in olfactory cells is related with this event, the particulate GC in these cells could be associated with the transduction of stimuli which could not be detected.The presence of both GC and AC at the surface of olfactory mucosa in association with olfactory cells could be indicative that the two enzymes have complementary activities in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified an adenylate cyclase (AC) that mediates olfactory transduction for a wide variety of odorants through cAMP as second messenger in olfactory cells of bullfrog and rat (Anholt, 1988;Lowe et aL, 1989;Pfeuffer et al, 1989;Ronnett et aI., 1991), and recently AC activity was detected in olfactory cells of rat ultracytochemically (Asanuma & Nomura, 1991).…”
Section: Introductionmentioning
confidence: 99%